Water energy nexus in the people republic of China and emerging issues. - Perera,Pradeep (Asian Development Bank, 2017)
Water and energy are both valuable resources and indispensable for human society and economic development. By nature, water and energy are interlinked. Water plays a critical role in the generation of electricity for cooling of thermal power plants and in hydropower, as well as in the production of fossil fuels such as coal; energy is required to treat, distribute, and for wastewater treatment. Choices made in either of the sectors may have unintended and often negative implications on the other sector.